Piperlongumine induces apoptosis and autophagy in human lung cancer cells through inhibition of PI3K/Akt/mTOR pathway. (September 2015) - Wang, Feng; Mao, Yong; You, Qingjun; Hua, Dong; Cai, Dongyan
Piperlongumine (PL), a natural alkaloid present in the fruit of the Long pepper, is known to exhibit notable anti-cancer effects. Nonetheless, the anti-tumor effect of PL in lung cancer cells still remains unclear. In the present study, we reported the chemotherapeutic effects of PL using in vitro and in vivo models. We showed that PL displayed potent anti-neoplastic activity against lung cancer A549 cells as well as corresponding docetaxel-resistant A549/DTX cells. In addition, we found that PL induced apoptosis in both A549 and A549/DTX cells. PL also induced autophagy in A549/DTX cells. Moreover, autophagy-specific inhibitors (3-methyladenine) or Beclin1 and Atg 5 small interfering RNAs (siRNAs) enhanced PL-induced apoptosis, indicating that PL-mediated autophagy may protect A549/DTX cells from undergoing apoptotic cell death. Furthermore, we observed the inhibition of phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) pathway by PL. Finally, PL inhibited the growth of A549/DTX xenograft tumors, which was associated with inhibition of cell proliferation, induction of apoptosis of tumor cells and decreased expression of p-Akt and p-mTOR in tumor xenograft tissues. In summary, our study demonstrated that PL induced apoptosis and autophagy through modulation of the PI3K/Akt/mTOR pathway in human lung cancer cells. This study may provide a rationale for future clinical application using PL as a chemotherapeutic agent for lung cancer.